Peran Guru PAI Sebagai Pembimbing Dalam Pembinaan Sopan Santun Peserta Didik di Madrasah Aliyah Sunan Ampel Pare Kediri - Dhuha Rohmawan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The role of education, especially a teacher, is very necessary for forming and cultivating character in students. The teacher as a role model for his students in shaping provides examples of good character so that they can produce good generations as well. Responding to the problems that occur, the author conducts research with the title